2012
DOI: 10.1111/j.1365-2427.2012.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal aquatic–terrestrial transitions in the temporary Albarine River, France: responses of invertebrates to experimental rewetting

Abstract: 1. In temporary rivers, viewed as coupled terrestrial-aquatic ecosystems, spatial and temporal transition zones between aquatic and terrestrial conditions are common and occur simultaneously. 2. The effects of artificial rewetting on terrestrial and aquatic invertebrate assemblages were examined in dry sediments collected from the Albarine River, France. Rewetted sediments had previously been dry for between 0.1 and 142 days. Dry sediments were collected directly from the streambed (DS) and from riparian grave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…Declines in the diversity and abundance of invertebrates emerging from sediments as the duration of drying increases have been observed in several studies (e.g. Larned et al 2007;Datry et al 2012). Also, Jenkins and Boulton (2007) found that for microinvertebrate egg banks, drying for a period greater than 10-20 years resulted in marked declines in species richness.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Declines in the diversity and abundance of invertebrates emerging from sediments as the duration of drying increases have been observed in several studies (e.g. Larned et al 2007;Datry et al 2012). Also, Jenkins and Boulton (2007) found that for microinvertebrate egg banks, drying for a period greater than 10-20 years resulted in marked declines in species richness.…”
Section: Introductionmentioning
confidence: 76%
“…Decanting was repeated at days 20 and 30. A 30 day duration was chosen as sufficient to stimulate hatching and emergence in most species, based on similar studies (Jenkins and Boulton 2007;Larned et al 2007;Chester and Robson 2011;Datry et al 2012). These studies all used similar methods of inundation with non-chlorinated water, decanting and filtering with the exception that, as in Jenkins and Boulton (2007), samples were not aerated because the sediments were from lentic rather than lotic habitats.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Aquatic and terrestrial species colonize and emigrate from intermittent rivers in response to shifts between wet and dry habitat (Acuña et al, 2005;Corti and Datry, 2012;Datry et al, 2012;Davey and Kelly, 2007;Steward et al, 2011). A smaller number of intermittent river specialists persist through multiple wet-dry cycles; this group includes aestivating fish and encysting invertebrates (Kikawada et al, 2005;Perry et al, 2008;Sayer, 2005).…”
Section: T H Snelder Et Al: Regionalization Of Patterns Of Flow Inmentioning
confidence: 99%
“…Some crustaceans produce drought resistant eggs or cysts (Datry et al, 2012;Stubbington & Datry, 2013). Other groups, such as many large predators (e.g.…”
Section: Introductionmentioning
confidence: 99%